The guide to electronic futures trading - Slutsky, Scott (McGraw-Hill, 2000)
"The Complete Guide to Electronic Futures Trading will help you quickly, seamlessly move from the phone and trading pit into today's fast-developing electronic futures marketplace. Its practical, nuts-and-bolts details cover everything from what hardware and software you'll need to techniques for finding the right broker for your individual trading needs and style."--BOOK JACKET.